Women in agriculture work for longer hours than those not into agriculture - Kumar, Anil; Sarkar, Ananta (Indian Council of Agricultural Research, 2023)
Work participation of women is governed by social norms, which places on them an unfair burden of unpaid work, thereby reducing the opportunity to participate in gainful employment; acquiring new skills; or indulge in leisure, socialization, or recreational activities. The discourse on women’s emancipation also needs to look into the underlying intersectionality like social groups, economic status, religion, etc. Within this ambit, it is also necessary to know how those women who practice agriculture differ from those who do not. Using the unit-level data of the first time-use study held in 2019 in India involving 137,730 males and 134,319 females in rural areas, we report the daily work pattern of men and women practicing agriculture contrasted with those who do not. We found that women practicing agriculture work for 622 minutes per day as opposed to 515 minutes for those who do not.